ANALYSIS OF EARLY CHILDHOOD EDUCATION MANAGEMENT IN THE INTERNALIZATION OF ECOLOGICAL-RELIGIOUS MORAL VALUES AT RAUDHOTUL ATHFAL - Kuni Niswatas Sholeha; Finadatul Wahidah; Zety Yusmira (AL-MAFAZI: JURNAL MANAJEMEN PENDIDIKAN ISLAM, 2024)
Early childhood education at RA Al Muarif Al Mubarok Jember is designed to shape character by integrating ecological-religious values, which is expected to equip them with environmental awareness and solid religious foundations. The research approach is qualitative with a case study type of research. The data collection technique uses interviews, observation, documentation, and data analysis using Miles and Huberman. The results of the study are the planning stages of managing early childhood education in the internalization of Moral Ecological-Religious Values ​​at RA Al Muarif Al Mubarok, which includes formulating the vision and mission of RA Al Muarif Al Mubarok Jember, developing integrated teaching modules, learning methods with an interactive and based approach: experience, involvement of parents and planning evaluation. The organizational stages carried out by RA Al Muarif Al Mubarok Jember cover various aspects to ensure that educational activities run smoothly and effectively according to the stated objectives. Organizing includes, among others, The organizational structure of RA Al Muarif Al Mubarok Jember and Tatib RA Al Muarif Al Mubarok Jember. The implementation stages of the management of Early Childhood Education in the Internalization of Ecological-Religious Moral Values ​​at RA Al Muarif Al Mubarok Jember are implementing a curriculum that has been designed whose content integrates ecological-religious moral values ​​as a whole—implemented through various activities, namely Daily Activities, Weekly Activities, Monthly Activities, Annual Activities. This educational evaluation stage is done through: 1. Regular Madrasah Supervision Program; 2. KKG at RA Al Muarif Al Mubarok Jember is carried out once a month; 3. Implementation of FGD; 4. Curriculum evaluation: Daily Evaluation, Semester Evaluation, Annual Evaluation; 5. RA Al Muarif Al Mubarok Jember carries out three types of assessments: diagnostic, summative, and formative.